Analisis Tantangan Dalam Pelaksanaan Pemungutan Pajak Pada PT. Kereta Api Indonesia (Persero) Daerah Operasi 8 Surabaya - Puspita, Vania Eka; Ikaningtyas, Maharani (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research analyzes the challenges in the implementation of tax collection at PT. Kereta Api Indonesia (Persero) Surabaya Operation Area 8. As a state-owned company PT. Kereta Api Indonesia (Persero) has significant tax obligations, including tax deposits and reporting. The challenges faced include the complexity of tax regulations, limited competent human resources, and the need for more sophisticated information technology. This research uses a qualitative descriptive approach to explore the inhibiting factors and provide strategic recommendations. This research is expected to help companies improve tax effectiveness and compliance.